Pemilihan Kepala Daerah : Regulasi, Model Komunikasi Dan Pendidikan Politik Di Aceh - Zainuddin T (Sadida Islamic Communications and Media Studies, 2025)
The direct election of regional heads in Aceh, which began in 2006, has become a significant milestone in Indonesia's democratic journey, particularly in post-conflict Aceh. This electoral model reflects the uniqueness of Aceh as a region with special autonomy, and serves as a laboratory for democracy in Indonesia. However, the implementation of the election was marked by significant challenges, such as regulatory complexity, local political dynamics, and the development of a democratic culture. The participation of former members of the Free Aceh Movement (GAM) in the 2006 local elections received special attention as part of the implementation of the Helsinki Memorandum of Understanding (MoU) agreed upon in 2005. This research aims to examine the regulations governing the local elections in Aceh. The research method used is qualitative. The results obtained indicate that the implementation of regulations in the regional head elections in Aceh includes the implementation of the Aceh Government Law (UUPA). This grants special authority in the administration of regional head elections. This authority regulates local values, community traditions, and local political dynamics, as well as alleviating the ongoing political situation.